Analisis Efektivitas dan Optimalisasi Penyelenggaraan Operasional Layanan Publik Kapal Perintis: (Studi Kasus : Pangkalan Ambon Provinsi Maluku) - Ahmad Lazim; Dian Junita Arisusanty; Femmy Asdiana; Rizqi Aini Rakhman; Alwi Sina Khaqiqi (Journal Of Business, Finance, and Economics (JBFE), 2025)
Perintis sea transportation is one of the government programs specifically to support 3TP regional connectivity. One of the implementation locations is in Pangkalan Ambon, Maluku Province, supported by a state subsidy budget. The results of the actualization of the program showed that several route segments were overlapping, cargo and passenger occupancy was not optimal and other technical problems. Given these problems, research was carried out to evaluate programs and efforts to optimize pioneering sea transportation. This research aims to provide modeling for measuring the effectiveness and optimization efforts carried out so that the useful value of the pilot program can increase. The method used in this research is quantitative descriptive. The results of this research show that there are five indicators in selecting effectiveness, including annual frequency, total operating time, number of goods, number of passengers and ship load factor. Based on the calculations and modeling that have been carried out, of the 17 route sections, there are 4 route sections that are ineffective, 3 route sections are quite effective, and 10 route sections are effective. To increase this effectiveness, investigative efforts that can be carried out include local regional government coordination by exploring regional potential, improving supporting facilities and infrastructure and adding a team of perintis oordinators.